Population dynamics of Steneotarsonemus concavuscutum, a neglected mite pest in coconut fruits (Cocos nucifera) - de França-Beltrão, Girleide V.; Monteiro, Vaneska B.; Melo, José W. S.; Lima, Debora B.; Lofego, Antônio C. [UNESP]; Gondim, Manoel G. C. (Springer Nature, 2023)
The meristematic region of Cocos nucifera fruits can be colonized by various species of mites, including Steneotarsonemus concavuscutum, Steneotarsonemus furcatus, and Aceria guerreronis. The consequence of this colonization is the development of necrotic lesions on the fruit, and sometimes its abortion. Losses are commonly attributed to A. guerreronis alone, owing to the similarities in the injuries caused and its predominance in coconut plantations. However, S. concavuscutum may be the predominant pest species in some crops. Despite the possible impact of S. concavuscutum, little is known about its bioecological aspects, such as the influence of biotic and abiotic factors on its population dynamics. Our objective was to document macroclimatic abiotic factors (temperature, relative humidity, and precipitation) and biotic factors (interspecific competition and predation) interfere in the population dynamics of S. concavuscutum. We evaluated the diversity and abundance of mites in the perianth of coconut fruit naturally infested by S. concavuscutum for 1 year. The species found in the fruits of bunch 6 of the plant, which is the fruit age at which the mites commonly reach the highest abundance, were counted every 2 weeks. We found mites from nine families and S. concavuscutum was the predominant species, representing about 92% of the individuals collected. Predators represented approximately 2% of the total collection, with Neoseiulus baraki as the predominant species. Steneotarsonemus concavuscutum population density ranged from 60 to 397 mites/fruit. The highest population densities of S. concavuscutum were observed in the hottest and driest periods of the year. The population densities of S. concavuscutum were negatively associated with the presence of N. baraki, suggesting that this predator may have a role in the biological control of this pest.
Keywords: Cocos nucifera; Neoseiulus baraki; Pest mite; Population fluctuation; Tarsonemidae